Exploração de basalto na região das Missões do estado do Rio Grande do Sul - Gehlen, Ibanor Volmir (2007)
In this work, they were described the approaches indication in the phases of solicitation/liberation of the extraction areas, as well as the evolutionary sequence of the appearance of the responsible organs for the environmental legislation of the areas of the quarries of basalt in Brazil. In the sequence the current reservation of basalt exploration was quantified in the quarries legalized in the Missions region of Rio Grande do Sul. The applicable work stages were described in the process of extraction of basalt and characterized the available technological present time in a located quarry of basalt in the municipality district of Cerro Largo/RS. The studies accomplished in this work aim the readiness of reservation of basalt in the Missions region of Rio Grande do Sul